Restrukturisasi Kapital Dalam Rangka Optimalisasi Industri Tekstil dan Produk Tekstil di Pusat Ekonomi Bandung - Maqin, Abdul; Djulius, Horas; Wahyuniardi, Rizki (Jurnal Trikonomika, 2012)
The symptoms of deindustrialization in recent years has made government of Indonesia to plan undertaking concrete steps to address it. In the context of MP3EI for Java corridor, one of the main economic activities in Central for Economic Bandung, is the textile industry.Framework set out in this study explained that the textile industry was thought to have a good resistance in the provision of inputs and the output market. Based on the urgency, the research focused on several factors i.e the productivity of capital, government policy on textile sector and businesses accessibility to sources of financing in an effort to restructure the textile machinery. The method used was qualitative research and conducted in two phases, accordance with the purposes of this study. The first phase was to identify and map the current conditions of the productivity of capital in the textile industry, especially businesses that were included in a small scale. The second phase was undertake efforts to expand opportunities for the businesses included in the restructuring program. One of the studyâs findings revealed that most SMEs have limitations in revitalizing the textile machine. This occured because their business were considered not bankable.